Indicators of Scene Changes in Persian and English Audio Descriptions: A Comparative Study - Salehi, Sina; Mousavi Razavi, Mir Saeed (International Journal of Linguistics and Translation Studies, 2023)
This study investigated the audio description (AD) of scene changes indicators in English and Persian ADs to determine the degree to which they conform to ITC Guidance on Standards for Audio Description and their similarities and differences. The Persian ADs included Persian dubbed versions of Casablanca, On the Waterfront, Psycho, and Citizen Kane, audio described in Persian, and the Iranian film Sorkhpust. The English ADs consisted of Bruce Almighty, Seven, and Fury films. Twenty minutes of each film were randomly selected to be analyzed with respect to the ITC[1] (2000). ITC suggests that appropriate indicators must signal scene changes. The results showed that scene changes in both English and Persian ADs were at times signaled by appropriate indicators and were also ignored at times. In the English ADs, the percentage for signaling scene changes was 62.83%; the number was 53.33% in the Persian ADs. This difference was caused by a higher frequency of short, simple temporal, and spatial scene change indicators in the English ADs. Also, another possible reason that can account for the difference is the potential differences in the subjective interpretations of change of location, which can lead to different perceptions of scene changes and the differences in the percentages of using indicators. [1] Independent Television Commission